Sources of Fluctuations in Relative Prices: Evidence from High Inflation Countries - Rogers, John H.; Wang, Ping (The Review of Economics and Statistics, 1993)
Casual analysis of six high-inflation episodes indicates a strong positive relationship between movements in the relative price ratio, measured by (WPI/CPI), and the inflation rate. The authors estimate a vector autoregression model in which relative price movements are driven by several fundamental disturbances (fiscal, monetary, output, and exchange rate), identified using only long-run restrictions based on a general-equilibrium optimizing model. Analysis of the endogenous response of relative price changes to these disturbances suggests that output and monetary shocks are the most important driving forces, although fiscal and exchange rate shocks are also influential in explaining relative price movements in some countries. Copyright 1993 by MIT Press.